Treatment of Leptomeningeal Disease with Tepotinib in a Patient with Lung Adenocarcinoma Harboring MET Exon 14 Skipping Mutation Presenting with Extensive Metastasis Involving Duodenum - Jacquelyn Shugarts; Aida Amado; Taylor Praska; Monica Camou; Jiaxin Niu (Reports)
Background and Clinical Significance: The mesenchymal–epithelial transition (MET) exon 14 skipping mutation (METex14) is a rare genetic alteration occurring in non-small cell lung cancer (NSCLC). Tyrosine kinase inhibitors (TKIs) are the approved treatment for first-line therapy in a metastatic setting. However, the unusual presentation of gastrointestinal metastasis and leptomeningeal carcinomatosis (LMD) poses significant treatment challenges. Case Presentation: Here we report a case of a 72-year-old male with metastatic METex14-positive NSCLC, presenting with brain and duodenal metastases. Conclusions: The patient responded exceptionally well to first-line chemoimmunotherapy, achieving clinically complete remission for 2 years. He subsequently developed cerebellar metastasis and leptomeningeal disease (LMD) but demonstrated a remarkable response to tepotinib and continued to enjoy radiographic complete remission over 2.5 years at the time of this report.